Feasibility of Measuring Context Specific Sedentary Behavior and Pulse Wave Velocity in Endometrial Cancer Survivors - Lauren C. Bates-Fraser PhD; Jake C. Diana MA; Aiden J. Chauntry PhD; Victoria L. Bae-Jump MD, PhD; Michelle L. Meyer PhD; Justin B. Moore PhD; Hyman B. Muss MD; Claudio L. Battaglini PhD; Lee Stoner PhD; Erik D. Hanson PhD (Integrative Cancer Therapies)
Purpose: Sedentary behavior (SB) contributes to the heightened risk of cardiovascular disease (CVD) in endometrial cancer survivors (ECS). This feasibility study aimed to evaluate key outcomes to assess the practicality of SB reduction interventions for ECS. Secondary aims included SB domain assessment and preliminary efficacy testing of the relationship between SB and arterial stiffness. Methods: Forty stage-1 ECS (BMI ≥ 25.0 kg/m², aged 50-80, <12 months post-treatment) participated in the study, which measured total and domain-specific SB using accelerometry and ecological momentary assessment (EMA). Aortic pulse wave velocity (PWV) was estimated via Mobil-O-Graph, and linear regression models examined the association between SB and PWV. Results: The study achieved 4 of 5 assessed outcomes, with a 63% consent rate in 10 months. Retention was high, with 90% of participants completing all aspects. Fidelity was strong, though EMA compliance was 69%, slightly below the 70% target. Self-reported SB was 71.4% lower than accelerometer-measured SB [MD: −5.00 hours/day (95% CI: −6.57 to −3.43), P  < .001]. ECS exhibited a PWV of 9.04 ± 1.80 m/s, 13.4% higher than normative values, with occupational SB significantly associated with PWV. Conclusions: This study highlights high SB and PWV levels in ECS, indicating the need for interventions, particularly for occupational SB. The high retention and consent rates suggest ECS are willing to engage in behavior change, pointing to future research focusing on strategies to reduce SB and improve cardiovascular health.